Adapting Alzheimer Disease and Related Dementias Clinical Research Evaluations in the Age of COVID-19. (April 2021) - Loizos, Maria; Neugroschl, Judith; Zhu, Carolyn W.; Li, Clara; Sewell, Margaret; Kinsella, Michael T.; Aloysi, Amy; Grossman, Hillel; Schimming, Corbett; Martin, Jane; Sano, Mary
Abstract : In March 2020, the novel coronavirus (COVID-19) became a global pandemic that would cause most in-person visits for clinical studies to be put on pause. Coupled with protective stay at home guidelines, clinical research at the Icahn School of Medicine at Mount Sinai Alzheimer's Disease Research Center (ISMMS ADRC) needed to quickly adapt to remain operational and maintain our cohort of research participants. Data collected by the ISMMS ADRC as well as from other National Institute on Aging (NIA) Alzheimer Disease centers, follows the guidance of the National Alzheimer Coordinating Center (NACC). However, at the start of this pandemic, NACC had no alternative data collection mechanisms that could accommodate these safety guidelines. To stay in touch with our cohort and to ensure continued data collection under different stages of quarantine, the ISMMS ADRC redeployed their work force to continue their observational study via telehealth assessment. On the basis of this experience and that of other centers, NACC was able to create a data collection process to accommodate remote assessment in mid-August. Here we review our experience in filling the gap during this period of isolation and describe the adaptations for clinical research, which informed the national dialog for conducting dementia research in the age of COVID-19 and beyond.